Appropriate prescribing in older people. Issue 1 (February 2014) - Penge, Justin; Crome, Peter
Summary Prescribing for older people is often complex and challenging. With age, people almost invariably develop diseases leading to the prescription of drugs and the risk of multiple prescribing increases, especially if there is strict adherence to single disease guidelines. There remains a paucity of evidence from clinical trials as to the efficacy of many drugs in patients aged over 80 years due to the gross under-representation of older people in clinical trials. Older people are also at increased risk of adverse drug events, which are an important cause of morbidity and mortality. A significant percentage of these are both predictable and potentially avoidable. In this updated review the concept of appropriate prescribing in older people is explored, including the importance of individualized care and shared decision-making. The available tools to enhance prescribing practice are examined, including those aimed at reducing inappropriate prescriptions and under prescribing. The limitations of existing tools are discussed and areas with particular promise and scope for advancement are highlighted, including the development of integrated IT systems and software engines to aid clinicians in appropriate prescribing.